Purification and characterization of a 1,2,4-trihydroxybenzene 1,2-dioxygenase from the basidiomycete Phanerochaete chrysosporium. - Rieble, S (1994)
1,2,4-Trihydroxybenzene (THB) is an intermediate in the Phanerochaete chrysosporium degradation of vanillate and aromatic pollutants. A P. chrysosporium intracellular enzyme able to oxidatively cleave the aromatic ring of THB was purified by ammonium sulfate precipitation, hydrophobic and ion-exchange chromatographies, and native gel electrophoresis. The native protein has a molecular mass of 90 kDa and a subunit mass of 45 kDa. The enzyme catalyzes an intradiol cleavage of the substrate aromatic ring to produce maleylacetate. 18O2 incorporation studies demonstrate that molecular oxygen is a cosubstrate in the reaction. The enzyme exhibits high substrate specificity for THB; however, catechol cleavage occurs at approximately 20% of the optimal rate. THB dioxygenase catalyzes a key step in the degradation pathway of vanillate, an intermediate in lignin degradation. Maleylacetate, the product of THB cleavage, is reduced to beta-ketoadipate by an NADPH-requiring enzyme present in partially purified extracts.